SRSLY?? A typology of online ironic markers. Issue 7 (19th May 2022) - Gal, Noam; Kampf, Zohar; Shifman, Limor
ABSTRACT: Social media constitute a fertile though challenging arena for the use of ironic humor. A combination of facilitating and hindering factors turns the production and identification of irony in this sphere into a complex venture, positioning it as a powerful tool in consolidating group boundaries. The main aims of this paper are to identify the markers of ironic humor on social media and to explicate their workings within the dynamics of digital interactions. Existing literature about ironic markers addresses mostly face-to-face and mass-mediated interactions, while there is a gap in our understanding of the production and interpretation of irony in the unique communicative conditions of social media. An analysis of a bilingual corpus of successful and failed ironic utterances extracted from five social network sites yielded a novel typology of five ironic markers: platform, participants, style, intra-textual content, and contextual knowledge. These markers both resemble and deviate from features of irony in non-digital settings. Media affordances often allow access to necessary complementary information, yet such forensic activity is only accessible to active users, who recognize the need for further investigation of the meant. Hence, using certain types of ironic markers forms utterances that are decipherable to some audiences but opaque to others. In this sense, the marking of digital irony and its decoding both rely on group boundaries and play a central role in their delineation. We conclude by evaluating the roles of this new regime of ironic markers in processes of boundary work.